Studying audience effects in animals: what we can learn from human language research. (February 2017) - Coppinger, Brittany; Cannistraci, Ryan A.; Karaman, Ferhat; Kyle, Steven C.; Hobson, Elizabeth A.; Freeberg, Todd M.; Hay, Jessica F.
Highlights: Animal audience effect studies often focus on rate and latency changes in signals. Human audience effect studies focus on fine-grained changes in signals. Fine-grained analysis answers a broader range of questions about audience effects. Animal behaviour research could benefit from fine-grained signal analyses.